Autonomy, Territory, Mobility: Everyday (Geo)Politics in Voluntary Exchange Networks - Anthony Ince (L'Espace Politique)
In this paper, I examine mobile territorial practices among participants in two global voluntary exchange networks. CouchSurfing (a hospitality network) and WWOOF (an organic farming network) are part of a broad spectrum of alternative travel economies rooted in global networks of mutual aid between and among hosts and guests. Using ethnography and interviews, I examine the extent to which the everyday practices and imaginaries of participants offer new configurations of, and relations to, mobility and territoriality. Mobility and territory have been conventionally positioned as opposed to one another, but recent work in geography has emphasised the contested co-constitution of movement/borderlessness and fixity/enclosure. The counter-territorial practices of Couchsurfing and WWOOF participants may, therefore, indicate ways of imagining and creating global collectivities and solidarities that counteract prevailing statist-capitalist territorial logics and relations. Deploying a critical framework drawn from the anarchist tradition, I interrogate the extent to which the autonomous “infrapolitics” of WWOOF and CouchSurfing participants offer alternative modes of living and relating globally.